ANÁLISIS DEL CIERRE DE CANALES DE TDT IMPUESTO POR EL TRIBUNAL SUPREMO ESPAÑOL DESDE LA PERSPECTIVA DE LAS EMPRESAS AFECTADAS - Dra. María-Jesús DÍAZ-GONZÁLEZ,Dra. Natalia QUINTAS-FROUFE (Fonseca, Journal of Communication, 2023)
On the 6th May 2014 nine nationally broadcast Digital Terrestrial TV (DTT) channels stopped broadcasting. The reason was the sentence imposed by the Supreme Court which considered these channels to be lacking the necessary licence. The objective of this article is to carry out a rigorous and critical analysis of this action. The analysis is from the point of view of the affected broadcasting companies, the law which covers the rights of these channels and how they communicated this information to their audiences. The analysis reaches the conclusion that the sentence is highly questionable and that it presents a backward step for the stability of DTT in Spain.